THE IMPACT OF CLASS REPETITION ON STUDENTS’ ACADEMIC ACHIEVEMENT: IMPLICATIONS FOR EDUCATIONAL POLICY MAKING - V.N, Eboatu; Omenyi, Ada Sam (European Scientific Journal, ESJ, 2015)
This paper reports the results of the study on the impact of class repetition on academic achievement of junior secondary school students (JSS) in Anambra State, Nigeria from 2004/2005 to 2006/2007 academic sessions. Three research questions and two null hypotheses guided this study, which adopted the Ex-Post-Facto research design. Stratified random sampling technique was used to select a sample of 149 failed JSS1 students in 2004/2005 session who repeated JSS1 in 2005/2006. A researcher designed inventory was used to collect data on these students’ results which were analysed using frequency counts, range of scores, percentage and Pearson Product Moment Correlation (r) for answering the research questions. t-test statistics was used to test the null hypotheses. The result of analysis showed that the repeated students performed well in their repeated JSS1 and did even better in their JSS2. Based on the results, it was recommended amongst others that the school administrators adopt an eclectic class promotion policy that would not rigidly apply mass promotion of all failed students.